2020
DOI: 10.7203/sjp.28.2.17848
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of examining the relationship between shape data and biologically meaningful variables. An example studying allometry with geometric morphometrics

Abstract: H. 2013. On the importance of examining the relationship between shape data and biologically meaningful variables. An example studying allometry with geometric morphometrics.[Importancia de investigar la relación entre la forma y variables con sentido biológico. Un ejemplo estudiando la alometría con morfometría geométrica].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Importantly, the power of GM increases when aiming to test the statistical covariation of shape with possibly related factors (Bookstein, 1991), yet this has seldom been exploited by any biological or paleontological discipline, in spite of its immense potential to aid discovery (Monteiro, 1999;Marugán-Lobón et al, 2013). Here we have shown that bipedal dinosaur trackways not only can be easily compared statistically and graphically using 2D GM, but also that the observed variation across trackways can be factored out to gain further insight.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, the power of GM increases when aiming to test the statistical covariation of shape with possibly related factors (Bookstein, 1991), yet this has seldom been exploited by any biological or paleontological discipline, in spite of its immense potential to aid discovery (Monteiro, 1999;Marugán-Lobón et al, 2013). Here we have shown that bipedal dinosaur trackways not only can be easily compared statistically and graphically using 2D GM, but also that the observed variation across trackways can be factored out to gain further insight.…”
Section: Discussionmentioning
confidence: 98%
“…We also tested if the trackway shape differences and the estimated speed differences are statistically associated with size (i.e., size is the real scale of the trackway) using multivariate and bivariate linear regressions (Monteiro, 1999;Marugán-Lobón et al, 2013), respectively. These tests are a rough proxy to asking if trackway geometry and movement speed are related to the size of the producing dinosaur.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they found in their study that at the peak of the adolescent growth spurt, skeletal development was more advanced in females compared to males, but that at the end of the spurt, females had a less mature skeletal development than males [30]. The assumption that the appropriate measurement of size is the size of the anatomical structure analysed, usually evaluated as the centroid size of a landmark configuration, is encountered in many morphometric analyses [10][11][12]16]. Centroid size is a composite measure of size based on all the landmarks and is proportional to the square root of the summed square interlandmark distances.…”
Section: Discussionmentioning
confidence: 99%
“…CS is a scalar accounting for the actual distance (in the actual scale of each specimen) between the landmarks and the centroid of the configuration (the geodesic centre of the configuration). The most common measure of size utilised in GM is centroid size (CS), which is the square root of the summed square distances between all the landmarks and their centroid [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation